2020
DOI: 10.1159/000507377
|View full text |Cite
|
Sign up to set email alerts
|

A Common Metric for Self-Reported Severity of Personality Disorder

Abstract: Introduction: Dimensional models of personality disorders (PD) in the DSM-5 and ICD-11 share a focus on impairments in self and interpersonal functioning to represent the general features and severity of PD. This new perspective has led to the development of numerous measures for assessing individual differences in PD severity. While this improves choices for researchers and practitioners, it also poses the challenge of an increasing lack of standardization. Objective: The aim of this study is to establish a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 70 publications
10
68
0
9
Order By: Relevance
“…From a psychodynamic viewpoint, the inclusion of severity of impairment as the core feature of personality disorder classification represents a major improvement over previous classification systems. Multiple studies have confirmed global severity as the single most important predictor for current and future dysfunction (37)(38)(39). The consideration of the severity of personality pathology also has been a central component of psychodynamic approaches to personality pathology for decades.…”
Section: Severitymentioning
confidence: 99%
See 2 more Smart Citations
“…From a psychodynamic viewpoint, the inclusion of severity of impairment as the core feature of personality disorder classification represents a major improvement over previous classification systems. Multiple studies have confirmed global severity as the single most important predictor for current and future dysfunction (37)(38)(39). The consideration of the severity of personality pathology also has been a central component of psychodynamic approaches to personality pathology for decades.…”
Section: Severitymentioning
confidence: 99%
“…But the results also show that the SASPD predominantly captures externalizing, interpersonal difficulties, while somewhat neglecting the area of self-functioning and internal distress. Additionally, Zimmermann et al (39) raised concern about the reliability of the SASPD to measure personality pathology severity when compared to 5 other self-report instruments derived from DSM-5 (LPFS-Brief Form 2.0, LPFS-Self Report, Personality Inventory for DSM-5-Brief Form Plus) and the psychodynamic tradition (IPO-16, OPD-SQS), arguably equally due to its lack of incorporation of items assessing the selfrelated dimension of personality functioning. Accordingly, the authors found a stronger correlation between the psychodynamic instruments and the AMPD of DSM-5 than with the ICD-11 system (39).…”
Section: Assessment Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Um grave transtorno da personalidade tem sido determinado por prejuízos severos na constituição do self, com problemas na integração da identidade e no autogoverno, bem como por prejuízos graves nos estilos de relacionamento interpessoal, com problemas na empatia e intimidade. Esses novos modelos estão intrinsecamente alinhados com o modelo de OP de Kernberg [22][23][24] . De fato, um estudo inclusive encontrou itens no IPO que cobrem todos os construtos do modelo alternativo de diagnóstico dos transtornos da personalidade descritos no DSM-5 1 .…”
Section: Discussionunclassified
“…The current study sought to investigate the utility of the PID5BF+M total score along with specific domain and facet scores in differentiating patients with PDs from other psychiatric patients. The use of the PID5BF+ as a proxy of severity is particularly supported in a comparative study by Zimmermann et al (22), which found the total PID5BF+ score to align well with a number of PD severity measures.…”
Section: Introductionmentioning
confidence: 90%